CONSIDERAÇÕES SOBRE A CAPTAÇÃO DE ÁGUA SUBTERRÂNEA NA REGIÃO CRISTALINA DO SEMI-ÁRIDO CEARENSE - UMA ALTERNATIVA - Gonçalves, J. Y. B.; Cordeiro, W.; Holanda, C. H. N. (Águas Subterrâneas, 1984)
INDISPONÍVEL